Ground ice, organic carbon and soluble cations in tundra permafrost soils and sediments near a Laurentide ice divide in the Slave Geological Province, Northwest Territories, Canada - R. Subedi; S. V. Kokelj; S. Gruber (The Cryosphere, 2020)
The central Slave Geological Province is situated 450–650 km from the presumed spreading centre of the Keewatin Dome of the Laurentide Ice Sheet, and it differs from the western Canadian Arctic, where recent thaw-induced landscape changes in Laurentide ice-marginal environments are already abundant. Although much of the terrain in the central Slave Geological Province is mapped as predominantly bedrock and ice-poor, glacial deposits of varying thickness occupy significant portions of the landscape in some areas, creating a mosaic of permafrost conditions. Limited evidence of ice-rich ground, a key determinant of thaw-induced landscape change, exists. Carbon and soluble cation contents in permafrost are largely unknown in the area. Twenty-four boreholes with depths up to 10 m were drilled in tundra north of Lac de Gras to address these regional gaps in knowledge and to better inform projections and generalizations at a coarser scale. Excess-ice contents of 20 %–60 %, likely remnant Laurentide basal ice, are found in upland till, suggesting that thaw subsidence of metres to more than 10 m is possible if permafrost were to thaw completely. Beneath organic terrain and in fluvially reworked sediment, aggradational ice is found. The variability in abundance of ground ice poses long-term challenges for engineering, and it makes the area susceptible to thaw-induced landscape change and mobilization of sediment, solutes and carbon several metres deep. The nature and spatial patterns of landscape changes, however, are expected to differ from ice-marginal landscapes of western Arctic Canada, for example, based on greater spatial and stratigraphic heterogeneity. Mean organic-carbon densities in the top 3 m of soil profiles near Lac de Gras are about half of those reported in circumpolar statistics; deeper deposits have densities ranging from 1.3–10.1 kg C m −3 , representing a significant additional carbon pool. The concentration of total soluble cations in mineral soils is lower than at previously studied locations in the ...